PELAKSANAAN IHDAD BAGI ISTERI YANG DI TINGGAL MATI MENURUT MAZHAB SYAFI’I (STUDI KASUS DI KECAMATAN PERCUT SEI TUAN KABUPATEN DELI SERDANG) - Muhammad Syukri Albani Nasution; Hasbullah Ja'far; Ismail Marjuki Harahap (Al-Mashlahah: Jurnal Hukum Islam dan Pranata Sosial, 2020)
ABSTRACTIslamic law provides a firm statement about a woman who has to undergo a period of ihdad as a sign of grieving for a specified time, in Article 170. In this case, the concept of ihdad and the consequences associated with it, has created problems in its application, as happened. in the Swimming Village, Percut Sei Tuan District, Deli Serdang Regency. In the community of Kolam Village, Percut Sei Tuan District, Deli Serdang Regency, the application of ihdad has been ignored by various kinds of arguments from the community. The steps used in this research are starting from data collection, both primary and secondary. These data will be traced in the literature deemed relevant. After the researchers analyzed, it was concluded that the implementation of ihdad for women whose husbands died in the district. Percut Sei Tuan Kab. Deli Serdang varies among them because of: a) Going out of the house and making decorations because of work demands. and stay at home and do not make up if you do not work for a month. b) Going out of the house and making decorations because of the demands of work. and remain at home and do not make up if not working, but less than a month, c) Going out of the house and make up because of the demands of work. and going out of the house and decorating as usual even if not while working for less than a month. Understanding the concept of ihdad for women whose husbands died in the Kec. Percut Sei Tuan Kab. Deli Serdang, including: a) Religion, b) Economic conditions, c) Conditions of employment (SOP), d) Community Habits (Urf) and d) Psychology.Keyword: Ihdad, Syafi'i School, Kab. Deli Serdang.